2011
DOI: 10.1016/j.amjsurg.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased hip flexion using stirrups on lower-extremity venous flow: a prospective observational study

Abstract: Background Patient positioning during operations for colorectal cancer may represent an unrecognized risk factor for deep venous thrombosis. Methods Twelve healthy control patients were positioned supine with knee flexion at 90°. Duplex ultrasound examined common femoral vein (CFV) and proximal femoral vein (PFV) diameter, peak systolic velocity, and volume-flow with hip flexion at 0°, 30°, 60°, and 90°. Data were analyzed using the paired t-test. Results In the CFV, hip flexion to 90° was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…in a study of laparoscopic and open gastric bypass surgery, it was also shown that surgical positions of the patient could lead to vein stasis 11 . in 12 healthy men aged 20-50 years who were positioned in colorectal surgery positions with 0º, 30º, 60º, 90º of hip flexion and abduction, the diameter of proximal femoral vein was shown to become smaller as the hip flexion advanced, leading to increase in femoral vein flow velocity 17 . These findings partially disagree with our results because our data demonstrated that the diameter of femoral vein was decreasing and flow velocity getting faster as the hip was more flexed at 30-60º position.…”
Section: Discussionmentioning
confidence: 96%
“…in a study of laparoscopic and open gastric bypass surgery, it was also shown that surgical positions of the patient could lead to vein stasis 11 . in 12 healthy men aged 20-50 years who were positioned in colorectal surgery positions with 0º, 30º, 60º, 90º of hip flexion and abduction, the diameter of proximal femoral vein was shown to become smaller as the hip flexion advanced, leading to increase in femoral vein flow velocity 17 . These findings partially disagree with our results because our data demonstrated that the diameter of femoral vein was decreasing and flow velocity getting faster as the hip was more flexed at 30-60º position.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, it was shown that the flow of CFV was significantly reduced during intraperitoneal insufflation, but not during preperitoneal insufflation [16]. Recently, the behavior of femoral venous flow in other types of open surgery has also been investigated [17,18]. Finally, it is interesting to know how epidural anesthesia compensates for the reduction of femoral flow detected when the laparoscopic technique is carried out under general anesthesia [19].…”
Section: Discussionmentioning
confidence: 96%
“…Peter et al . demonstrated that hip flexion of 90° maximizes venous drainage from the legs . VTE prophylaxis guidelines in plastic surgery issued by the American Society of Plastic and Reconstructive Surgeons also reported that knee flexion of 5° can maximize popliteal venous flow .…”
Section: Discussionmentioning
confidence: 97%
“…The formation of CO 2 pneumoperitoneum during laparoscopic surgery is transmitted to the retroperitoneum, inferior caval vein and iliac veins, leading to slower flow in veins of the lower extremities. Increased chest pressure also has been observed, which could affect cardiac filling, thus in turn impeding venous flow, inducing venous stasis, and activating coagulation and fibrinolysis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation